1998
DOI: 10.1099/0022-1317-79-5-1069
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and co-encapsidation of human immunodeficiency virus type 1 Gag and Vif recombinant proteins.

Abstract: Human immunodeficiency virus type 1 (HIV-1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(119 citation statements)
references
References 44 publications
7
110
0
2
Order By: Relevance
“…Although immunofluorescence studies showed a co-localization of Gag and Vif in the cell (38), co-sedimentation studies indicated an interaction of Vif only with some early viral assembly intermediates, and the presence of Vif in mature virions remains controversial (39 -46). In insect cells infected with baculovirus expressing Gag and Vif, it was estimated that there were 70 Vif molecules per 2000 Gag molecules in extracellular Gag particles or one molecule of Vif for every 30 molecules of Gag (47). If single Gag molecules bound to Vif at this same ratio within an APOBEC3G/Vif/Gag complex destined for degradation in the proteosome, this would account for only 3.5% of Gag molecules produced, and a change in Gag distribution in the cell would not be detectable by our Western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…Although immunofluorescence studies showed a co-localization of Gag and Vif in the cell (38), co-sedimentation studies indicated an interaction of Vif only with some early viral assembly intermediates, and the presence of Vif in mature virions remains controversial (39 -46). In insect cells infected with baculovirus expressing Gag and Vif, it was estimated that there were 70 Vif molecules per 2000 Gag molecules in extracellular Gag particles or one molecule of Vif for every 30 molecules of Gag (47). If single Gag molecules bound to Vif at this same ratio within an APOBEC3G/Vif/Gag complex destined for degradation in the proteosome, this would account for only 3.5% of Gag molecules produced, and a change in Gag distribution in the cell would not be detectable by our Western blot assay.…”
Section: Discussionmentioning
confidence: 99%
“…In certain cases, polyclonal anti-GAG antibody (laboratory-made; see Ref. 25) was used. Antiserum against HEED was prepared in rabbit, by injection of purified HEEDNt120 -535 protein obtained by affinity purification of GST-fused protein as described above.…”
Section: Gel Electrophoresis and Immunological Analysesmentioning
confidence: 99%
“…38) was used for biopanning onto immobilized protein ligate. Specific ligand elution of phages has been described in previous studies (25,39,40). Purified MA143 was immobilized on enzyme-linked immunosorbent assay plates used as the solid support.…”
Section: Phage-displayed Hexapeptide Library and Biopanningmentioning
confidence: 99%
See 2 more Smart Citations